2019
DOI: 10.1074/mcp.ra119.001392
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin L Regulates Metabolic Networks Controlling Rapid Cell Growth and Proliferation

Abstract: Remodeling of cellular metabolism is a genuine feature of rapidly growing cells. Herein we report that mouse embryonic fibroblasts, lacking the Cathepsin L (Cts L) gene, proliferate faster than wild-types and display a noticeable glycolytic shift to satisfy their ever-growing metabolic needs. Mass spectrometry analyses identified LDHA as an essential metabolic junction in these cells, and downstream biochemical studies suggested that Cts L regulates LDHA expression and function. Together, these data uncover an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…It may be speculated that this is at least partly due to enhanced glycolytic activity. In line with these data, a recently published study in murine embryonic fibroblasts also revealed that cathepsin L inhibition led to a shift in cellular energy production towards glycolysis [79].…”
Section: Discussionsupporting
confidence: 66%
“…It may be speculated that this is at least partly due to enhanced glycolytic activity. In line with these data, a recently published study in murine embryonic fibroblasts also revealed that cathepsin L inhibition led to a shift in cellular energy production towards glycolysis [79].…”
Section: Discussionsupporting
confidence: 66%
“…It is unclear, however, whether the repertoire of substrates is the same for single-chain and two-chain cathepsin L. Shifting the balance from the two-chain to single-chain form upon legumain inhibition could possibly account for some of the changes that we observed in both our preTAILS and TAILS analyses. Recent work by Weiss-Sadan has demonstrated a role for cathepsin L in the regulation of metabolism and mitochondrial dynamics. , In our preTAILS analysis, we identified a number of mitochondrial proteins associated with a metabolic activity that were differentially regulated upon legumain inhibition. These observations could be at least partially explained by the effects of legumain on cathepsin L. The prevalence of P1 arginine residues among the cleavage events identified in both DMSO- and LI-1-treated cells may be driven by the activity of cathepsin L or other cysteine cathepsins.…”
Section: Discussionmentioning
confidence: 94%
“…Recent work by Weiss-Sadan has demonstrated a role for cathepsin L in the regulation of metabolism and mitochondrial dynamics. 48,49 In our preTAILS analysis, we identified a number of mitochondrial proteins associated with a metabolic activity that were differentially regulated upon legumain inhibition. These observations could be at least partially explained by the effects of legumain on cathepsin L. The prevalence of P1 arginine residues among the cleavage events identified in both DMSO-and LI-1-treated cells may be driven by the activity of cathepsin L or other cysteine cathepsins.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Cathepsin B (CATB), a lysosomal protease, is overexpressed in human breast cancers with high metabolic activity and is correlated with poor prognosis. Cathepsin B is a also regulator of metabolic processes [125]. It has been shown that HIF1A is involved in the modulated glycolytic activity.…”
Section: Poly I:cmentioning
confidence: 99%